Pengaruh Penerapan Media Trainer Kendali Motor Modular Terhadap Pemahaman Mahasiswa Pada Mata Kuliah Praktik Pengaturan & Penggunaan Motor Listrik Di Universitas Negeri Medan - Arbi Azizi Lubis, Reza; Purba, Sukarman; Syaputri, Kartika; Ayuvi, Maulana (Jurnal Etnik: Ekonomi-Teknik, 2023)
This study aims to determine the effect of the application of a modular electric motor control media trainer on student understanding in the practice course of setting up and using electric motors. This study used a quasi-experimental method with a pretest-posttest control group design. The research subjects were PTE-C class students as the experimental class and PTE-A students as the control class with 20 students each in each class. Research data were analyzed using the Paired Sample T-Test. The results showed that there were significant differences between students' understanding before and after participating in learning with the modular electric motor control media trainer in the experimental class. Meanwhile, in the control class that did not use a modular motor control media trainer, there was no significant difference between students' understanding before and after participating in the lesson. From the results of this study, it can be concluded that the modular electric motor control media trainer has a significant influence on students' understanding in the practical setting and use of electric motors courses. Modular motor control media trainers can be presented as an effective alternative learning media to increase student understanding of the subject.